Role of health literacy in the clinical outcomes of the elderly: a scoping review (Research, Society and Development, 2021)
Population aging is natural, complex and with variables that directly affect the quality of life of the elderly and society. Health literacy is a relatively new concept, which seeks to characterize the individual's ability to understand and be an active agent of their health-disease process. Thus, the aim was to verify the relationship between health literacy and clinical outcomes presented by the elderly population. The Scope Review method was used as recommended by the Joanna Briggs Institute. Data collection was performed in the databases Brazilian Virtual Health Library (BVS) and Pub Med. We used the descriptors “literacy”, “letramento”, “alfabetización en salud”, “elderly”, “aged”, “idoso”, “anciano”, “clinical outcomes” and “health outcomes”. The search resulted in the selection of 19 articles for the review, being verified the relationship of health literacy with various clinical outcomes, principally, systemic arterial hypertension, diabetes mellitus, heart failure, cardiovascular risk, chronic obstructive pulmonary disease, admissions and hospitalizations mild cognitive impairment, Alzheimer's disease and depression. Outcomes related to pain and disability were not related to health literacy. The literature has pointed out an important relationship between health literacy and several relevant clinical outcomes in the patient's clinical context, being a valuable factor in the clinical evaluation of the elderly.